The expression of IGFBP-5 in the reproductive axis and effect on the onset of puberty in female rats - Zhiqiu Yao; Maosen Lin; Tao Lin; Xinbao Gong; Pin Qin; Hailing Li; Tiezhu Kang; Jing Ye; Yanyun Zhu; Qiwen Hong; Ya Liu; Yunsheng Li; et al. (BMC, 2022)
Abstract Insulin-like growth factor-binding protein-5 (IGFBP-5) has recently been shown to alter the reproductive capacity by regulating insulin-like growth factor (IGF) bioavailability or IGF-independent effects. The present study aimed to investigate the effect and mechanism of IGFBP-5 on the onset of puberty in female rats. Immunofluorescence and real-time quantitative PCR were used to determine the expression and location of IGFBP-5 mRNA and protein distribution in the infant's hypothalamus-pituitary-ovary (HPO) axis prepuberty, peripuberty, puberty and adult female rats. Prepubertal rats with IGFBP-5 intracerebroventricular (ICV) were injected to determine the puberty-related genes expression and the concentrations of reproductive hormones. Primary hypothalamic cells were treated with IGFBP-5 to determine the expression of puberty-related genes and the Akt and mTOR proteins. Results showed that Igfbp-5 mRNA and protein were present on the HPO axis. The addition of IGFBP-5 to primary hypothalamic cells inhibited the expression of Gnrh and Igf-1 mRNAs (P < 0.05) and increased the expression of AKT and mTOR protein (P < 0.01). IGFBP-5 ICV-injection delayed the onset of puberty, reduced Gnrh, Igf-1, and Fshβ mRNAs, and decreased the concentrations of E2, P4, FSH,serum LH levels and the ovaries weight (P < 0.05). More corpus luteum and fewer primary follicles were found after IGFBP-5 injection (P < 0.05).